Face stability analysis of a shallow horseshoe-shaped shield tunnel in clay with a linearly increasing shear strength with depth. (March 2020) - Zhang, Chengping; Li, Wei; Zhu, Wenjun; Tan, Zhibiao
Highlights: A continuous velocity field for a horseshoe-shaped shield tunnel is proposed. The proposed horseshoe-shaped model effectively improves the face stability. An improved velocity field for a horseshoe-shaped shield tunnel is proposed. Abstract: The face stability of a horseshoe-shaped shield tunnel in undrained clays with a linearly increasing strength is numerically and analytically investigated in this paper. Based on the kinematic approach of limit analysis, a continuous velocity field for a horseshoe-shaped shield tunnel is proposed to evaluate the limit support pressure of both the collapse and blow-out of the tunnel face. Moreover, the analytical results are compared with those obtained from the numerical simulation and other existing literatures. The results show that the horseshoe-shaped shield tunnel can improve the face stability compared to the circular shield tunnel. Finally, an improved velocity field is proposed, which provides a more realistic failure pattern and a better upper bound solution of the limit support pressure for the horseshoe-shaped shield tunnel.